PROFIX: método de avaliação on-line da proficiência digital - Marques Junior, Euro [UNESP]; Oliveira Neto, José Dutra de; Marques, Emilia de Mendonça Rosa [UNESP] (My University, 2014)
The Digital Proficiency level is a measure of how effectively individuals and organizations engage with digital technology for their own benefit, and their internal and external customers. There are certification programs to identify those levels through practical tests, thus informing the digital competences of an individual associated with computer knowledge and Internet usage. Such certification and evaluation programs are not easily accessible due to the cost of application or the distance from the test site. The PROFIX method presented in this article, is also a tool for assessing the level of digital proficiency, and was developed to overcome those difficulties. This approach is based on an online survey with questions related to the main components of Digital Proficiency. In this article it also presents a comparative case study of the use of PROFIX by university students and professors, and elementary school teachers in Brazil (n = 440).The usage of this method associated with a course or distance training, provides teachers and educational designers with prior knowledge about Digital Proficiency levels, individual and collective and enables them to propose online activities appropriate to the group's profile. Also allows the planning of support and training actions about the information and communication technologies so that these contribute effectively in the formation of students in courses that use resources of Distance Education through the Internet. Thus, this method is available to the public free of charge and can be offered online, facilitating the access. PROFIX is quite flexible and can be adapted for use other public sectors (bank customers, employees, users of social networks etc.).

O nível de Proficiência Digital é uma medida de quão efetivamente indivíduos e organizações se envolvem com a tecnologia digital para o benefício próprio, e de seus clientes internos e externos. Existem programas de certificação para identificar esses níveis através de testes práticos, informando assim as competências digitais de um indivíduo associadas aos conhecimentos de informática e uso da Internet. Tais programas de certificação e avaliação não são facilmente acessíveis, devido ao custo de aplicação ou a distância do local dos testes. O método PROFIX, apresentado nesse artigo, é também um instrumento para a avaliação do nível de Proficiência Digital, e foi desenvolvido visando superar essas dificuldades. Esse método se baseia em um survey on-line com questões relacionadas aos componentes principais da Proficiência Digital. Nesse artigo apresenta-se ainda um estudo de caso comparativo da utilização do PROFIX por estudantes e professores universitários e também professores do ensino fundamental no Brasil (n=440). O uso desse método associado a um curso ou treinamento a distância, permite aos professores e designers educacionais o conhecimento prévio dos níveis de Proficiência Digital, individuais e dos grupos, possibilitando aos mesmos proporem atividades on-line adequadas ao perfil do grupo. Permite ainda o planejamento de ações de apoio e treinamento para que as tecnologias de informação e comunicação contribuam efetivamente na formação dos estudantes de cursos que utilizem recursos de Educação a Distância (EAD) através da Internet. Dessa forma, o método está disponível ao público gratuitamente, e pode ser proposto de modo on-line, facilitando o acesso. O PROFIX é bastante flexível e pode ser adaptado para ser usado por outros públicos (clientes de bancos, funcionários, usuários de redes sociais etc.).
Keywords: Digital proficiency; ICT literacy; Distance education; On-line evaluation; Proficiência digital; Literacia em TIC; Educação a distância; Avaliação online